Padang City's Leading Creative Industry: Increasing Competitiveness In The Asian Market - Harahap, Erni Febrina; Rahmi, Siti; Amelianda Putri, Winny; Basri Tanjung, Ranni (Universitas Gorontalo, 2026)
The creative economy is often associated with small and medium-sized enterprises (SMEs), that have been important to a nation's or region's economy (Harahap et al., 2022). Both developed and developing countries' economies depend heavily on SMEs because of their contribution to the expansion of each country's gross domestic product (Harahap et al., 2020). More creative industry business units than other city districts can be found in Padang City, one of the West Sumatra Province’s cities (West Sumatera Tourism Office, 2021). Where these SMEs also absorb more labor than large-scale businesses. Increasing the competitiveness of this creative industry is needed to boost the increase in regional income and community welfare. This study aims to assess and identify the top creative industries, consider Padang City's potential and obstacles to making its creative industries more competitive, and analyze the roles of the three stakeholders in the creative industry—the community, entrepreneurs or academics, and the government. The research method uses Comparative Advantage, Analytical Hierarchy Process (AHP), and SWOT analysis.